Development and internal validation of clinical prediction models for outcomes of complicated intra-abdominal infection. Issue 4 (22nd February 2021) - Ahmed, S; Bonnett, L; Melhuish, A; Adil, M T; Aggarwal, I; Ali, W; Bennett, J; Boldock, E; Burns, F A; Czarniak, E; Dennis, R; Flower, B; et al.
Abstract: Background: Complicated intra-abdominal infections (cIAIs) are associated with significant morbidity and mortality. The aim of this study was to describe the clinical characteristics of patients with cIAI in a multicentre study and to develop clinical prediction models (CPMs) to help identify patients at risk of mortality or relapse. Methods: A multicentre observational study was conducted from August 2016 to February 2017 in the UK. Adult patients diagnosed with cIAI were included. Multivariable logistic regression was performed to develop CPMs for mortality and cIAI relapse. The c-statistic was used to test model discrimination. Model calibration was tested using calibration slopes and calibration in the large (CITL). The CPMs were then presented as point scoring systems and validated further. Results: Overall, 417 patients from 31 surgical centres were included in the analysis. At 90 days after diagnosis, 17.3 per cent had a cIAI relapse and the mortality rate was 11.3 per cent. Predictors in the mortality model were age, cIAI aetiology, presence of a perforated viscus and source control procedure. Predictors of cIAI relapse included the presence of collections, outcome of initial management, and duration of antibiotic treatment. The c-statistic adjusted for model optimism was 0.79 (95 per cent c.i. 0.75 to 0.87) and 0.74 (0.73 to 0.85) for mortality and cIAI relapse CPMs. Adjusted calibration slopes were 0.88 (95 per cent c.i. 0.76 to 0.90) for the mortality model and 0.91 (0.88 to 0.94) for the relapse model; CITL was −0.19 (95 per cent c.i. −0.39 to −0.12) and − 0.01 (− 0.17 to −0.03) respectively. Conclusion: Relapse of infection and death after complicated intra-abdominal infections are common. Clinical prediction models were developed to identify patients at increased risk of relapse or death after treatment, these now require external validation. Abstract : This observational study was undertaken by the National Infection Trainee Collaborative for Audit and Research and is one of the largest studies on complicated intra-abdominal infection (cIAI) undertaken in the UK. It shows that infection relapse and mortality is common after treatment. Data from the study were used to develop and internally validate clinical prediction models for relapse and death in patients treated for cIAI. Infection relapse and mortality common